The Eurosceptical Reader 2 - Holmes, M. author. aut Link
XVI, 296 p. 16 illus.
Keywords: Europe is the biggest political issue in contemporary Britain. The contributions to this volume all express disapproval and doubt about the integration process. Some favour EU membership while rejecting the single currency; others favour renegotiation of Britain's relationship with the EU; others recommend withdrawal. But different preferred solutions do not obscure a commonality of belief that the status quo of EU membership, leading inexorably to a monetary and fiscal euroland, is undesirable and should be democratically resisted. Similarly Tony Blair's advocacy of a 'superpower' Europe is conceptually repudiated.